CONCEPTUAL ANALYSIS OF COOPERATIVE LEARNING STRATEGIES IN INDONESIAN LANGUAGE LEARNING IN THE SOCIETY 5.0 ERA: A STRUCTURED LITERATURE REVIEW - Rossy Widya Puspita; Fira Triana Annisa; Sindy Alfiana; Ahmad Faizi; Iwan Marwan; Harfiandi Harfiandi (Jurnal Visipena, 2025)
This study aims to conduct a conceptual analysis of cooperative learning strategies and examine their relevance to Indonesian language instruction in the Society 5.0 context. Educational transformation in the Society 5.0 era requires learning strategies that not only emphasize content mastery but also foster collaboration, critical thinking, creativity, and artificial intelligence (AI) literacy. Although cooperative learning has been widely implemented in Indonesian language education, integrative conceptual studies linking cooperative learning with Deep Learning pedagogy, AI integration, and the Pancasila Student Profile (P5) remain limited. This research employed a structured literature review of scholarly publications published between 2018 and 2025, identified using the keywords cooperative learning, Indonesian language learning, Society 5.0, Deep Learning, and artificial intelligence. Data analysis was conducted through data reduction, categorization, and thematic synthesis to construct an integrative conceptual framework. The findings indicate that cooperative learning strategies are highly relevant to Society 5.0 learning demands, particularly in supporting student-centered learning, project-based instruction, and the development of 21st-century skills (4C). The integration of cooperative learning with Deep Learning principles namely mindful, meaningful, and joyful learning and the use of AI as a supportive tool for learning and assessment enhance the effectiveness of Indonesian language instruction. This study contributes a novel integrative conceptual model connecting cooperative learning, AI, Deep Learning, and P5, offering both theoretical insights and practical guidance for educators in designing adaptive and collaborative Indonesian language learning in the Society 5.0 era.